P217 Is it tuberculosis? evaluating diagnostic certainty using TB network cohort review. (December 2018) - Solomon, D; Gupta, RK; Abubakar, I; Booth, H; Dekoningh, J; Miller, RF; White, J; Lipman, M
Abstract : Background: The diagnosis of tuberculosis can be challenging, relying on a variable combination of clinical and laboratory features plus response to treatment. Misdiagnosis may lead to unnecessary TB drug toxicities in some patients and an untreated true underlying diagnosis in others. Culture confirmation is recommended, therefore, in >85% cases. We introduced a simple 'diagnostic certainty' score within our cohort review procedure to provide a measure of the confidence of each TB diagnosis by month 6–9 of treatment. Methods: The score was developed following consultation across our TB network (table 1). This was applied to each adult TB case discussed at cohort review from December 2016 – December 2017. We analysed these by patient demographics and TB disease characteristics to identify factors related to diagnostic certainty. Results: A total of 323 patients were started on TB treatment. Of these, 34 (10.5%) were subsequently de-notified, leaving 289 cases discussed at cohort review (median age 43, 46% female). The predominant ethnic groups were Black African (25.7%), White (23.8%) and Indian (14.6%). Approximately half were pulmonary (145/289; 50.2%). The most frequent extra-pulmonary disease sites were lymph node (56.4%), pleural (16.1%), bone (11%), GI/peritoneal (9.2%) and CNS (5%). More pulmonary than extra-pulmonary cases had a maximal diagnostic certainty score (positive culture or molecular test): 117/145 (80.7%) vs 74/144 (51.4%) respectively (Odds Ratio 3.95, CI 2.34–6.70, p<0.001). 15.2% (22/145) pulmonary and 28.5% (41/144) extra-pulmonary cases had a score of 2 or 1 (indicating possible, rather than probable or definite TB). There was no significant association between age, ethnicity, gender or social risk factors and odds of possible TB (a score of 2 or 1). Specific extra-pulmonary sites were not associated with a low diagnostic score. Conclusions: A simple diagnostic certainty score during cohort review provides a continuous metric of TB service quality and enables benchmarking. Extra-pulmonary TB significantly increases the likelihood of apparent diagnostic uncertainty (culture/molecular test negativity). This may reflect the difficulty of obtaining adequate specimens from extra-pulmonary sites, the low yield from current mycobacterial diagnostic technology or the mis-characterisation of a number of predominantly inflammatory conditions as 'active TB disease'.